PENEGAKAN HUKUM TERHADAP PELAKU PENYEBARAN VIDEO CALL SEX SEBAGAI ANCAMAN ATAS PENOLAKAN PINJAMAN UANG(Studi Putusan : Nomor 406/Pid.Sus/2023/PN.Tjk) - Mulia Wulan Sari; Baharudin Baharudin; Risti Dwi Ramasari (INTELIGENSIA MEDIA, 2025)
This study aims to analyze the factors that cause the occurrence of criminal acts of spreading video call sex as a threat of rejection of a loan and law enforcement against perpetrators of spreading video call sex as a threat of rejection of a loan made on social media based on the decision: number c 406 / Pid.Sus / 2023 / PN.Tjk. The research method used is a normative legal approach by analyzing court decisions and the relevance of applicable positive legal regulations. The results of the study show that there are three factors that influence the occurrence of acts of spreading sexual content, namely; economic factors, trust, and sexual education. And law enforcement related to this case can be seen from the provisions of Article 27 paragraph (1) in conjunction with Article 45 paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. That the Defendant was sentenced to 3 (three) years in prison and a fine of Rp. 10,000,000, - (ten million rupiah) with the provision that if the fine cannot be paid, it will be replaced with 3 (three) months in prison.